Komunikasi Simbolik Upacara Mapag Rare Di Dusun Pemunut Desa Suranadi Kecamatan Narmada Kabupaten Lombok Barat - I Nengah Putra Kariana; I Wayan Wirata; Ni Putu Sudewi Budhawati (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2019)
Mapag Rare Ceremony is a tradition or ceremony that continues to be carried out by the people in Pemunut. In the process of carryiod out mapag rare ceremony activity, of course there is a symbol that is communicated so that it can be understood by the people in Pemunut or who carried out the ceremony. The aims of this research is to uncover the form, process and meaning of the mapag rare ceremony which was carried out in Pemunut, Suranadi Village, Narmada District, West Lombok Regency. This research is a qualitative descriptive paradigm using the foundation of George Herbet Mead's symbolic Interactional theory and Koencaraningrat's religious theory. The teknick of collection the data is observation, interviews, and documentation. The location of this research in Pemunut, Suranadi Village, Narmada District, West Lombok Regency. The results of the reseachhowed that the form of communication carried out was a form of intrafersonal communication and interpersonal communication. The type of communication carried out is verbal and non verbal communication and transcendental communication is a type of ritual communication which is also a communication process in a mapag rare ceremony. The meaning of communication symbolic of a mapag rare ceremony is a meaning about self-cleansing born and bhatin and there is a religious meaning that is reflected through the procedures symbols used in the mapag rare ceremony, socio-cultural meaning reflected in the tradition of saling tulungin, pade gelahan, saling silihin and the meaning of education that is reflected in a brainstorm or sangkep in the process of preparing for the ceremony.